VALIDITY, RELIABILITY AND SENSITIVITY OF THE TEST STROKE WITH LEG MAE GERI - Elena Soklevska; Lulzim Ibri; Marko Zeljković; Žarko Kostovski; Boško Zaborski (University of Banja Luka, Faculty of physical education and sport, 2012)
Specific motor abilities in modern sport are probably the determining factor for solving sports tasks and achievingsport success. Strockes with an arm and leg in karate sport are dominant techniques which help a karate athlete toscore points or win a fight. Karate sport and particularly sports discipline fight (kumite) is characterized with polystructural movements, and the most important motor skills are explosiveness, speed and coordination. The subjectof this research derives from the previous knowledge and arguments and it is directed toward determination of themeasuring characteristics (reliability, sensitivity and validity) of the specific "Mae Geri" motor test.The research has been conducted in the Republic of Macedonia with an intentional sample of 30 male examinees(karate athletes), at the age older then 18. During the research with the sample of examinees, 1 (one) manifest specific-motor variable (newly constructed composite test) was applied, characteristic for the karate sport. The aim of thisresearch was to determine the measuring characteristics of the newly constructed test. Using the Hoteling method,the factor validity of this test was determined, as well as its latent dimensions, and the main component accordingto Kaiser-Gutman criterion were established. Based on the obtained results of the research, there have been someconclusions which refer to the measuring characteristics of the applied test, and primarily to the factor validity,sensitivity and reliability of the same.